Sistem Kehadiran Biometrik Sidik Jari Menggunakan IoT yang Terintegrasi dengan Telegram - Adipta Martulandi; Dedi Setiawan (Engineering, MAthematics and Computer Science (EMACS) Journal, 2021)
The rapid development of technology today is very useful for humans in various aspects of life. One of the impacts of these technological developments is IoT (Internet of Things). Currently, IoT has been widely used in various fields such as manufacturing, offices, public transportation, and education. One of the uses of IoT in the field of education is to create a biometric attendance system using fingerprints. The purpose why use the fingerprints is to reduce cheating committed by students such as leaving absent. By using the fingerprint IoT attendance system, this is difficult to do because everyone has a different form of fingerprint. In addition, this project integrates fingerprint attendance with the Telegram messenger application. All fingerprints and student attendance data are stored on the website. Based on the experimental results, the success rate of this attendance system is 80%, and the accuracy is 89%.